2023
DOI: 10.1007/s10639-023-11749-x
|View full text |Cite
|
Sign up to set email alerts
|

An extended hedonic motivation adoption model of TikTok in higher education

Abstract: As information technologies develop, social networking services have gradually gained attention from both researchers and practitioners. However, little is known about the technology adoption of social networking from the perspective of hedonic motivation. For this purpose, this study applied the hedonic motivation system adoption model (HMSAM) to TikTok and incorporated two innovative factors, i.e., perceived boredom and personal innovativeness. Via structural equation modeling (SEM), this study used SmartPLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
5
22
2
Order By: Relevance
“…In the context of entertainment live streaming, research hypothesis H6 confirms the positive impact of perceived usefulness on user curiosity, a finding also supported by previous studies [174][175][176][177][178][179]. In this study, perceived usefulness refers to consumers' perceptions of the pricing of dynamic decorations and the intended meanings behind them.…”
Section: The Value Enhancement Role Of Ar Technology In Network Enter...supporting
confidence: 84%
See 3 more Smart Citations
“…In the context of entertainment live streaming, research hypothesis H6 confirms the positive impact of perceived usefulness on user curiosity, a finding also supported by previous studies [174][175][176][177][178][179]. In this study, perceived usefulness refers to consumers' perceptions of the pricing of dynamic decorations and the intended meanings behind them.…”
Section: The Value Enhancement Role Of Ar Technology In Network Enter...supporting
confidence: 84%
“…Finally, the research has found that perceived usability significantly influences perceived usefulness, joy and other factors [175,176]. Simultaneously, perceived usefulness and perceived joy have a positive impact on consumers' purchase intention in a live streaming environment [116].…”
Section: The Influence Of Perceived Usefulness On Curiosity Perceived...mentioning
confidence: 92%
See 2 more Smart Citations
“…In this study, Chinese students who participated in a gamified eco-driving program reported higher levels of hedonic motivation, which, in turn, led to greater intention to adopt eco-driving behavior. The authors 60 suggested that hedonic motivation can enhance the benefits and enjoyment of eco-driving, increasing individuals' willingness to overcome the perceived costs and barriers of adopting this behavior. Therefore, it is important to design gamified interventions that consider young people's hedonic needs and preferences, as this can increase the effectiveness and appeal of these interventions.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%